2018
DOI: 10.3390/nu10070862
|View full text |Cite
|
Sign up to set email alerts
|

Kefir Supplementation Modifies Gut Microbiota Composition, Reduces Physical Fatigue, and Improves Exercise Performance in Mice

Abstract: The present study evaluated the potential beneficial effect of kefir (KF) against fatigue. Furthermore, the composition of the gut microbiota is related to health benefits in the host; therefore, the study also investigated the effect of KF on the gut microbiota composition. Male ICR mice from four groups (n = 8 per group) were orally administered KF once daily for four weeks at 0, 2.15, 4.31, and 10.76 g/kg/day and were designated as the vehicle, KF-1X, KF-2X, and KF-5X groups, respectively. The gut microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 51 publications
3
87
1
1
Order By: Relevance
“…Among the most popular probiotics, kefir (KF), a drink rich in lactic ferments obtained from the fermentation of milk, has been proposed against hypertension, GI diseases, allergies, ischemic heart disease [164,165], fatigue and fatigue-related metabolites [166,167], and exercise-induced immune suppression [168]. KF is able to lower plasma lactate, ammonia, and creatine kinase (CK) levels, increasing the exercise performance and counteracting physical fatigue in mice [169], altering gut microbiota composition.…”
Section: Probioticsmentioning
confidence: 99%
“…Among the most popular probiotics, kefir (KF), a drink rich in lactic ferments obtained from the fermentation of milk, has been proposed against hypertension, GI diseases, allergies, ischemic heart disease [164,165], fatigue and fatigue-related metabolites [166,167], and exercise-induced immune suppression [168]. KF is able to lower plasma lactate, ammonia, and creatine kinase (CK) levels, increasing the exercise performance and counteracting physical fatigue in mice [169], altering gut microbiota composition.…”
Section: Probioticsmentioning
confidence: 99%
“…As previous reports [26], post-exercise assessment of the effects of supplementation SA-03 on fatigue-related biochemical indicators, and accurate display and assessment of physiological status. Fatigue-related variables were measured under fasting conditions to reflect actual physiological fitness.…”
Section: Determination Of Fatigue-associated Biochemical Variablesmentioning
confidence: 65%
“…Furthermore, kefir administration has been shown to reduce physical fatigue and improve exercise performance in mice (Hsu et al 2018). A recent randomized, controlled trial has even shown that kefir can reduce bloating and improve mood in patients with inflammatory bowel disease (Yilmaz et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized, controlled trial has even shown that kefir can reduce bloating and improve mood in patients with inflammatory bowel disease (Yilmaz et al 2019). Finally, kefir has been shown to modulate the composition of the gastrointestinal microbiota in rodents (Kim et al 2017, Bourrie et al 2018, Hsu et al 2018, Gao et al 2019). Overall, current evidence indicates that the traditionally fermented milk drink kefir merits investigation to determine its ability to modulate the microbiota-gut-brain axis and affect the mood of the host.…”
Section: Introductionmentioning
confidence: 99%